THE IMPACT OF INSTAGRAM MARKETING ADOPTION TOWARDS CONSUMER PURCHASE DECISION ON FASHION - Daniel Augustinus; Agnes Agnes (Universitas Putera Batam, 2020)
Social networking sites have been emerged and transformed the world, bringing the world and its people closer. Social media which are part of social networking sites have become more effective in marketing tools; it helps in creating opportunities and awareness to consumers. Social media platform such as Instagram has recently become the most popular social networking sites among the young people. In addition, selling and market the products in the virtual store on Instagram represents a new shopping mode for most consumers, especially youngsters both men and women, and they represent an important role in influencing fashion consumer purchase decision through social networking sites. This study attempted to investigate impact of social networking sites towards consumer purchase decision on fashion industry. Therefore, questionnaires are spreaded out to 110 respondents who are social media users in Medan in order to gather the necessary information and data. The results of this research, it is concluded that social networking sites (the usability of Instagram) influences and give impact towards consumer purchase decision on fashion. Moreover, both of the variables have a strong relationship on each other and considered to be linear. The results also demonstrate that Instagram influences fashion consumer purchase decision through its usability such as good metrics, eye catching content, and recommendations from others. Furthermore, Instagram is also proved to have a positive impact towards consumer purchase decision by creating awareness, provide satisfaction feeling and creating virtual communities which may motivates consumer to do an online purchase.